Simulation of ultrasound two-dimensional array transducers using a frequency domain model - Rao, Min; Varghese, Tomy; Zagzebski, James A. (Medical physics (Lancaster), 2008)
Ultrasound imaging with two-dimensional (2D) arrays has garnered broad interest from scanner manufacturers and researchers for real time three-dimensional (3D) applications. Previously the authors described a frequency domain B-mode imaging model applicable for linear and phased array transducers. In this paper, the authors extend this model to incorporate 2D array transducers. Further approximations can be made based on the fact that the dimensions of the 2D array element are small. The model is compared with the widely used ultrasound simulation program FIELD II, which utilizes an approximate form of the time domain impulse response function. In a typical application, errors in simulated RF waveforms are less than 4 % regardless of the steering angle for distances greater than 2 cm, yet computation times are on the order of 1/35 of those incurred using FIELD II. The 2D model takes into account the effects of frequency-dependent attenuation, backscattering, and dispersion. Modern beam-forming techniques such as apodization, dynamic aperture, dynamic receive focusing, and 3D beam steering can also be simulated.